The relationship between women's experiences of mistreatment at facilities during childbirth, types of support received and person providing the support in Lucknow, India. (September 2016) - Diamond-Smith, Nadia; Sudhinaraset, May; Melo, Jason; Murthy, Nirmala
Abstract: Background: a growing body of literature has highlighted the prevalence of mistreatment that women experience around the globe during childbirth, including verbal and physical abuse, neglect, lack of support, and disrespect. Much of this has been qualitative. Research around the world suggests that support during childbirth can improve health outcomes and behaviours, and improve experiences. Support can be instrumental, informational, or emotional, and can be provided by a variety of people including family (husbands, mothers) or health providers of various professional levels. This study explores women's reported experiences of mistreatment during childbirth quantitatively, and how these varied by specific types of support available and provided by specific individuals. Methods: participants were women age 16–30 who had delivered infants in a health facility in the previous five years and were living in slums of Lucknow India. Data were collected on their experiences of mistreatment, the types of support they received, and who provided that support. Results: women who reported lack of support were more likely to report mistreatment. Lack of support in regards to discussions with providers and provider information were most strongly associated with a higher mistreatment score. Women who received any type of support from their husband or a health worker were significantly more likely to report lower mistreatment scores. Receiving informational support from a mother/mother-in-law or emotional support from a health worker was also associated with lower mistreatment scores. However, receiving emotional support from a friend/neighbour/other family member was associated with a higher mistreatment score. Conclusions: women rely on different people to provide different types of support during childbirth in this setting. Some of these individuals provide specific types of support that ultimately improve a woman's overall experience of her childbirth. Interventions aiming to reduce mistreatment to women during childbirth should consider the important role of increasing support for women, and who might be the most appropriate person to provide the most essential types of support through this process.